Implementasi Media Smartboard Dalam Menumbuhkan Kemampuan Literasi Budaya Anak Di TK-Alhidayah - aini, aini; Farida, Siti (Universitas Hamzanwadi, 2025)
This study aims to describe the implementation of smartboard media in fostering cultural literacy among early childhood students at TK Al-Hidayah. The background of this research is the lack of children's understanding of local culture due to conventional teaching methods. A descriptive qualitative method was used, with data collected through observation, interviews, and documentation. The research subjects were children aged 5–6 years. The results show that the use of smartboard media increased children's engagement in learning, strengthened their understanding of local culture, and fostered appreciation for cultural diversity. Children became more active, enthusiastic, and easily remembered cultural elements such as traditional clothing, songs, and houses. These findings indicate that smartboard media is an effective tool to support cultural education from an early age. Keywords: smartboard media, cultural literacy, early childhood, interactive learning, local culture